Penyuluhan Kesehatan sebagai Upaya Meningkatkan Literasi Masyarakat tentang ISPA di Kampung Ansudu I Kabupaten Sarmi - Sari, Eka Puspita; Dosinaeng, Antonius S.W.; Pureklolon, Paula S.M; Chuswarany, Muzdalifah P.; Tasik, Putri I.; Pekei, Amelia Y.; Tabuni, Alfian B.F.C; Sasarari, Anisa H.N.; Duwiri, Devega E.; Aliansyah, Dimas A.; et al. (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to increase public knowledge about Acute Respiratory Infections (ARI) through health education in Ansudu I Village, Sarmi Regency, enabling the community to take preventive measures and perform early management of ARI. The implementation method used a health education approach with a one-group pre-test–post-test design. Participants completed questionnaires before and after the health education session to measure changes in knowledge. Data were analyzed using the Paired T-Test. The target partners of this activity were residents of Ansudu I Village, including housewives, health cadres, and community leaders. The program focused on improving community literacy regarding ARI through health education. Before the intervention, the majority of respondents (69.2%) had low levels of understanding about ARI, whereas after the intervention, 53.8% of participants demonstrated good knowledge. The paired T-test produced a p-value of 0.000, indicating that the health education effectively increased community literacy about ARI.